How Long is the Safest InterDelivery Interval in Women with Previous History of Cesarean Delivery? - Budi I Santoso; Raymond Surya; Karina K Firdaus; Surahman Hakim (Indonesian Society of Obstetrics and Gynecology, 2018)
Objective: To investigate the association between interdelivery interval and uterine rupture in women with previous CD.   Methods: The formulation question was how long is the safest interdelivery interval to minimalize the risk of uterine rupture. The authors investigated in three databases including Pubmed, Cochrane, and Embase database. Inclusion criteria were abstract answering the clinical question, written in English language, and full-text paper availability.   Results: One systematic review, six cohort studies, and 1 casecontrol study were collected to compare the inter-pregnancy interval to the risk of uterine rupture. The author retrieved seven articles suitable to the inclusion criteria after excluding ten articles screened by the abstract and language. Then, the author added one article used in the systematic review. Hence, the critical appraisal based on Validity, Importance, and Applicability (VIA) was performed for eight articles.   Conclusion: The inter-delivery interval ï,³18 months is the safest time to avoid uterine rupture. Prostaglandin analogue induction should be avoided and for patients with a history of past cesarean using a single-layer closure to be educated about the increased risk. Keywords: cesarean delivery, inter-delivery interval, uterine rupture, vaginal birth after cesarean delivery